2001
DOI: 10.1080/000164801316878908
|View full text |Cite
|
Sign up to set email alerts
|

Radical Cavities and Cochlear Implantation

Abstract: Profoundly deaf patients with chronic suppurative otitis media have been contraindicated for cochlear implantation in the past. Complications such as infection of the radical cavity, fat necrosis, skin flap problems, change in electrode position and cholesteatoma have occurred in subjects with radical cavities. The aim is to create a dry, self-cleansing, infection-free cavity. This is essential in patients about to receive a cochlear implant, as infection may be introduced into the cochlea at the implantation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 2 publications
1
27
0
2
Order By: Relevance
“…It is not possible, therefore, to draw any conclusions with regard to which tissue type or technique, either a temporalis muscle flap or abdominal fat, results in a better outcome. Our long-term results, with respect to the complication rate, the need for revision, and the stability of the obliterated cavity, compare favorably with those of other published reports (14,16,17). Gray et al (10) reported the successful use of abdominal fat for obliteration in a series of 16 patients with CSOM.…”
Section: Discussionsupporting
confidence: 90%
“…It is not possible, therefore, to draw any conclusions with regard to which tissue type or technique, either a temporalis muscle flap or abdominal fat, results in a better outcome. Our long-term results, with respect to the complication rate, the need for revision, and the stability of the obliterated cavity, compare favorably with those of other published reports (14,16,17). Gray et al (10) reported the successful use of abdominal fat for obliteration in a series of 16 patients with CSOM.…”
Section: Discussionsupporting
confidence: 90%
“…Again, the authors had included various techniques including tympanostomy tube insertion, and follow-up was short, not exceeding 3. pit, graft abscess, and temporary facial nerve palsy. Finally, Hamzavi et al (2) reported 7 implanted cases of radical cavities using 1-step subtotal petrosectomy with obliteration and blind-sac closure of the external ear canal fixating the electrode array with muscle flaps and bone pate. The authors did not have any surgical complications.…”
Section: Discussionmentioning
confidence: 97%
“…In the past, cochlear implantation was contraindicated in such cases because of the perceived high risk of complications including infection, meningitis, cholesteatoma recurrence, and device extrusion. Gradually, several studies in the literature reported successful implantation in cases with chronic otitis media or atelectatic ears (1,2). However, most of these studies have assessed a small sample of patients during a short follow-up period (taking into account that complications may occur many years after implantation [3]) or have used various surgical techniques or included cases from different cochlear implant centers, making the results and any related conclusions weak and not generalizable.…”
mentioning
confidence: 97%
“…Assim, há risco de labirintite e infecção intracraniana nestes pacientes, pois a cóclea comunica-se com o espaço subaracnoide cerebral por meio do aqueduto coclear (Axon et al, 1997;Hamzavi et al, 2001;Ku et al, 2004;El-Kashlan e Telian, 2004;Kim et al, 2004;Incesulu et al, 2004;Basavaraj et al, 2005;Olgun et al, 2005;Leung, Briggs, 2007;Hellingman, Dunnebier, 2009;Postelmans et al, 2009;Kojima et al, 2010).…”
Section: Implante Coclear E Otite Média Crônica Supurativaunclassified
“…O manejo dos pacientes com OMC pode requerer extração de gordura abdominal, confecção de retalho pediculado de músculo temporal, aplicação de pó de osso, cimento de hidroxiapatita ou de fosfato tricálcio, para que a cavidade mastóidea possa ser obliterada, completa ou parcialmente, no mesmo tempo cirúrgico da implantação (Axon et al, 1997;Bendet et al, 1998;Hamzavi et al, 2001;Kim et al, 2004;Incesulu et al, 2004;Basavaraj et al, 2005;Olgun et al, 2005;Leung, Briggs, 2007;Postelmans et al, 2009;Kojima et al, 2010;Husseini et al, 2011), ou como primeira etapa. Posteriormente, o IC pode ser realizado como um procedimento de segunda fase, 3-6 meses após a cirurgia de obliteração (Axon et al, 1997;Bendet et al, 1998;Issing et al, 1998;Kim et al, 2004;Jenkins, Woodson, 2005;Olgun et al, 2005;Leung, Briggs, 2007;Postelmans et al, 2009;Kojima et al, 2010) ou até em 1 ano (Kim et al, 2004;Incesulu et al, 2004).…”
Section: Implante Coclear E Otite Média Crônica Supurativaunclassified